The Power of Influence and Reviews: Trust as a Key Factor in Shopee Consumers' Purchase Intention - Conny, Conny (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the influence of influencer marketing and online customer reviews on consumer purchase intention, while considering the role of trust as both a mediating and moderating variable. Using a quantitative approach and Partial Least Squares–based Structural Equation Modeling (SEM-PLS), this research involved 410 Shopee users in Kendari City as respondents. Data were collected through a questionnaire employing a Likert scale. The results indicate that both influencer marketing and online customer reviews have a significant direct effect on consumers' purchase intention. However, online customer reviews exert a stronger influence, both in shaping purchase intention and in enhancing consumer trust in the platform. Trust is also proven to play an important role as a mediator, strengthening the relationship between marketing strategies and purchase intention. On the other hand, trust does not function as a significant moderator in the relationship between influencer marketing and purchase intention. In contrast, the interaction between online customer reviews and influencer marketing shows a significant moderating effect, indicating that the combination of these two strategies can mutually reinforce their impact on consumers' purchase decisions. This study emphasizes the importance of building trust through authentic and credible strategies, particularly by leveraging positive online customer reviews, to enhance the effectiveness of digital marketing campaigns.